Curcuma longa polyphenols improve insulin‐mediated lipid accumulation and attenuate proinflammatory response of 3T3‐L1 adipose cells during oxidative stress through regulation of key adipokines and antioxidant enzymes. (20th April 2016) - Septembre‐Malaterre, Axelle; Le Sage, Fanny; Hatia, Sarah; Catan, Aurélie; Janci, Laurent; Gonthier, Marie‐Paule
Abstract: Plant polyphenols may exert beneficial action against obesity‐related oxidative stress and inflammation which promote insulin resistance. This study evaluated the effect of polyphenols extracted from French Curcuma longa on 3T3‐L1 adipose cells exposed to H2 O2 ‐mediated oxidative stress. We found that Curcuma longa extract exhibited high amounts of curcuminoids identified as curcumin, demethoxycurcumin, and bisdemethoxycurcumin, which exerted free radical‐scavenging activities. Curcuma longa polyphenols improved insulin‐mediated lipid accumulation and upregulated peroxisome proliferator‐activated receptor‐gamma gene expression and adiponectin secretion which decreased in H2 O2 ‐treated cells. Curcuminoids attenuated H2 O2 ‐enhanced production of pro‐inflammatory molecules such as interleukin‐6, tumor necrosis factor‐alpha, monocyte chemoattractant protein‐1, and nuclear factor κappa B. Moreover, they reduced intracellular levels of reactive oxygen species elevated by H2 O2 and modulated the expression of genes encoding superoxide dismutase and catalase antioxidant enzymes. Collectively, these findings highlight that Curcuma longa polyphenols protect adipose cells against oxidative stress and may improve obesity‐related metabolic disorders. © 2016 BioFactors, 42(4):418–430, 2016